Attitude Stabilization of Quadrotor with Input Time Delay. Issue 2 (2020) - Sharma, Manmohan; Kar, Indrani
Abstract: A predictor feedback control for attitude stabilization of quadrotors with input time delay has been proposed in this paper by representing the attitude using rotation matrices to avoid the singularities and ambiguities associated with Euler angles and quaternions. The closed loop system is shown to be asymptotically stable with respect to a norm defined in the text. The norm has been defined in terms of states and past control efforts and hence explicitly results in Lyapunov Krasovskii functional for the system. A cascade of PDE-ODE system and the concept of transport delay has been used in the proof.